Findings on the Evolution of Pre-and Post-Covid-19 Digital Payment Systems in Indonesia: Systematic Literature Review - Riskawati, Reni; Rebelia H. Savitri; Norazlina Abd Wahab (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
The role of cash as a means of payment has shifted due to technological advances towards digital payments which are more economical, efficient and effective. Online payment methods are one that is changing in the financial sector due to technological sophistication. The aim of this article is to provide an analysis and synthesis of the findings by conducting a systematic literature review, following the procedures prescribed by (SLR). Based on this procedure, we defined research questions and analysis questions that reflected the research objectives and delimited the scope of the study. The results of the research include findings regarding pre and post Covid-19 payments, problems and efforts to overcome the evolution of the payment digitalization system in Indonesia